Racjonalizacja religii i izolacja społeczna - Drozdowicz, Zbigniew (Polskie Towarzystwo Religioznawcze, 2011)
Zbigniew Drozdowicz – RATIONALIZATION OF RELIGION AND SOCIAL ISOLATION The relation between the rationalization of religion and social isolation had been analyzed and presented among others by Max Weber. In this article I recall not just his theses, but I also use them for the attempt of giving an answer to the question on social situation of those new religious movements, which by rationalizing their beliefs and practices either isolate themselves from the environment, or are being isolated. We may put under discussion the rationality of the rationali-zations proposed by these movements, as well the basis of their isolation (or the lack of it). The first one is a problem for most of the various kinds of philosophers and scholars, the latter one for those public institutions brought into existence to secure safety to the citizens. The position of those people might be considered as a guidance for the mentioned institutions.